Diagnosing lactose malabsorption in children: difficulties in interpreting hydrogen breath test results. (2nd March 2016) - Ruzsanyi, Veronika; Heinz-Erian, Peter; Entenmann, Andreas; Karall, Daniela; Müller, Thomas; Schimkowitsch, Alexander; Amann, Anton; Scholl-Bürgi, Sabine
Abstract: Lactose malabsorption (LM) is caused by insufficient enzymatic degradation of the disaccharide by intestinal lactase. Although hydrogen (H2 ) breath tests (HBTs) are routinely applied to diagnose LM, false-negative results are not uncommon. Thirty-two pediatric patients (19 females, 13 males) were included in this prospective study. After oral lactose administration (1 g kg −1 bodyweight to a maximum of 25 g), breath H2 was measured by electrochemical detection. HBT was considered positive if H2 concentration exceeded an increase of ⩾20 ppm from baseline. In addition to H2, exhaled methane (CH4 ), blood glucose concentrations and clinical symptoms (flatulence, abdominal pain, diarrhea) were monitored. A positive HBT indicating LM was found in 12/32 (37.5%) patients. Only five (41.7%, 5/12) of these had clinical symptoms during HBT indicating lactose intolerance (LI). Decreased blood glucose concentration increments (⩽20 mg dL −1 (⩽1.1 mmol L −1 )) were found in 3/5 of these patients. CH4 concentrations ⩾10 ppm at any time during the test were observed in 5/32 (15.6%) patients and in 9/32 (28.1%) between 1 ppm and 9 ppm above baseline after lactose ingestion. In patients with positive HBT 10/12 (83.3%) showed elevated CH4 (>1 ppm) above baseline in breath gas, whereas in patients with negative HBT this figure was only 4/17 (23.5%). In addition to determining H2 in exhaled air, documentation of clinical symptoms, measurement of blood glucose and breath CH4 concentrations may be helpful in deciding whether in a given case an HBT correctly identifies patients with clinically relevant LM.